A mass event of paraquat poisoning via inhalation - Shi, Mengdi; Zeng, Mei; Jian, Tianzi; Yu, Guangcai; Genjiafu, Aerbusili; Zhang, Xiangxing; Guo, Lanlan; Shang, Ruikai; Zhou, Zhiqiang; Zhang, Tongyue; Jian, Xiangdong; Kan, Baotian (Frontiers in Public Health, 2023)
Objective In January 2023, a rare event of collective inhalation paraquat poisoning occurred in Shandong, China. To analyze the clinical characteristics of an event of respiratory tract paraquat poisoning through inhalation. Methods Clinical data from eight patients with paraquat inhalation poisoning were retrospectively analyzed. Results The patients were mainly exposed to paraquat via the respiratory tract. The main clinical manifestations were ocular and respiratory irritation. Lung computed tomography (CT) showed that all eight patients had varying degrees of lung injury, mainly manifesting as exudative lesions. Laboratory tests revealed arterial blood gas hypoxemia, abnormal white blood cell count, and increased neutrophil ratio. Sufficient glucocorticoid impact therapy was effective, and all eight patients survived. Conclusion Eight patients experienced chest tightness, shortness of breath, and varying degrees of lung injury due to inhalation of paraquat through the respiratory tract. The early use of glucocorticoids and other comprehensive treatment measures, active prevention and treatment of lung infections, and protection of organ function have beneficial effects in such cases.